Hydro-ethanol extract of Holarrhena floribunda stem bark exhibits anti-anaphylactic and anti-oedematogenic effects in murine models of acute inflammation - Stephen Antwi; Daniel Oduro-Mensah; David Darko Obiri; Newman Osafo; Aaron Opoku Antwi; Helena Owusu Ansah; Augustine Ocloo; Laud K. N.-A. Okine (BMC, 2022)
Abstract Background Holarrhena floribunda (G.Don) T.Durand & Schinz stem bark has anecdotal use in Ghanaian folk medicine for the management of inflammatory conditions. This study was conducted to investigate the in vivo anti-inflammatory activity of the bark extract using models of acute inflammation in male Sprague Dawley rats, C57BL/6 mice and ICR mice. Methods A 70% hydro-ethanol extract of the stem bark (HFE) was evaluated at doses of 5-500 mg/kg bw. Local anaphylaxis was modelled by the pinnal cutaneous anaphylactic test. Systemic anaphylaxis or sepsis were modeled by compound 48/80 or lipopolysaccharide, respectively. Clonidine-induced catalepsy was used to investigate the effect on histamine signaling. Anti-oedematogenic effect was assessed by induction with carrageenan. Effects on mediators of biphasic acute inflammation were studied using histamine and serotonin (early phase) or prostaglandin E2 (late phase). Results HFE demonstrated anti-inflammatory and/or anti-oedematogenic activity comparable to standard doses of aspirin and diclofenac (inhibitors of cyclooxygenases-1 and -2), chlorpheniramine (histamine H1-receptor antagonist), dexamethasone (glucocorticoid receptor agonist), granisetron (serotonin receptor antagonist) and sodium cromoglycate (inhibitor of mast cell degranulation). All observed HFE bioactivities increased with dose. Conclusions The data provide evidence that the extract of H. floribunda stem bark has anti-anaphylactic and anti-oedematogenic effects; by interfering with signalling or metabolism of histamine, serotonin and prostaglandin E2 which mediate the progression of inflammation. The anti-inflammatory and antihistaminic activities of HFE may be relevant in the context of the management of COVID-19.